Demethylzelasteral inhibits proliferation and EMT via repressing Wnt/β-catenin signaling in esophageal squamous cell carcinoma - Yu, Jiarui (J Cancer, 2021)
As a kind of tumor commonly seen, no effective treatment is available for esophageal squamous cell carcinoma (ESCC). Therefore, seeking a new treatment is urgent. Demethylzeylasteral (T-96) isolated from Tripterygium wilfordii root bark embraces outstanding good antitumor activity. However, as for the mechanism of T-96 work on ESCC cells, it is rarely reported. In this study, we found that T-96 has inhibition when ESCC cells are proliferating, migrating and cloning. Moreover, relevant effects are influenced by dose and time. And T-96 can result in the stop of G2/M phase and induce apoptosis of ESCC cells. In addition, the expressions of Cyclin B1, Cyclin D1, Bcl-2, PARP1 and Survivin were decreased after starch demethylation. Despite of this, Bax and PARP1's expressions went up. To add up, there was an obvious increase in the expression of E-cadherin, while that of N-cadherin, Vimentin and MMP9 decreased after T-96 treatment. Moreover, the expression of Wnt/β-Catenin pathway, which concerns proteins β-Catenin, c-Myc and Wnt3a decreased. Our study shows that T-96 inhibits the proliferation and migration of esophageal cancer cells through Wnt/β-catenin pathway. Moreover, it gives rise to cell cycle arrest and apoptosis. According to the research results, T-96 tends to be put into use when treating ESCC patients, thus laying the experimental foundation for clinical research.